Home for the holidays - Foster, Jodie; Rajski, Peggy; Richter, W. D.; Hunter, Holly, 1958-; Downey, Robert, Jr., 1965-; Bancroft, Anne, 1931-2005; McDermott, Dylan; Chaplin, Geraldine, 1944-; Guttenberg, Steve, 1958-; Danes, Claire, 1979-; Stevenson, Cynthia, 1962-; Durning, Charles, 1923-2012; et al. (Santa Monica, CA MGM Home Entertainment, 2001)
Claudia Larson is a divorced single mom who just lost her job and now has to fly home for the traditional family Thanksgiving in Baltimore. From the plane, she calls for reinforcements--and her brother Tommy makes it down from Boston with a little surprise: a handsome friend named Leo. Between dropping the turkey in their sister's lap and a few fist fights on the front lawn, Claudia and Tommy recapture their childhood and Claudia and Leo explore the sweet possibility of romance.
Based on a short story by Chris Radant.
Originally produced as a motion picture in 1995.
Special features: Audio commentary by director Jodie Foster; theatrical trailer.
Director of photography, Lajos Koltai ; editor, Lynzee Klingman ; music, Mark Isham.
Holly Hunter, Robert Downey, Jr., Anne Bancroft, Dylan McDermott, Geraldine Chaplin, Steve Guttenberg, Claire Danes, Cynthia Stevenson, Charles Durning.
MPAA rating: PG-13.
Keywords: Adult children -- Drama; Thanksgiving Day -- Drama; DVD-Video discs; Feature films -- United States; Comedy -- Feature; Comedy films; Drama; Fiction films; Video recordings for the hearing impaired